Housing affordability and mental health: an analysis of generational change - Bentley, R; Baker, E; Ronald, R; Reeves, A; Smith, SJ; Simons, K; Mason, K (Taylor and Francis, 2022)
Unaffordable housing has many dimensions, not least its far-reaching implications for mental health. Although the psycho-social effects of housing affordability stress are well documented there is a lack of research on their variation within or between cohorts who have shared experiences of housing (social generations). This article fills that gap by following 14,000 Australians in the national Household, Income and Labour Dynamics survey for 16-years as they enter and exit unaffordable housing. We model when cohorts seem most vulnerable to mental health effects of unaffordable housing. We find contemporaneously that while people born in the 1980s have a high likelihood of falling below the affordability threshold, older people have a lower likelihood of recovering. These trends create a ‘pinch point’ for this older generation with negative mental health consequences. We position housing affordability stress as an indicator of precarity whose mental health effects may vary both within cohorts and between generations as a product of their shared experiences of housing.